Exploring Students’ Mathematical Literacy in Understanding and Applying Linear Equations: A Qualitative Inquiry in Indonesian Junior High Schools - Nurina Kurniasari Rahmawati; Arie Purwa Kusuma; Khoirunisah Khoirunisah; Zahratul Fauziah (Journal of Transdisiplinary Studies in Education, 2025)
Background: Mathematical literacy helps students link abstract reasoning to real situations, yet many still find it difficult to apply such understanding, especially when learning linear equations. Aims: This research explores how junior high school students understand and apply mathematical literacy when dealing with problems related to linear equations in one variable. It also aims to uncover the factors influencing their ability to reason, interpret, and express mathematical ideas within real-life contexts. Methods: The study used a qualitative descriptive design involving twenty-five eighth-grade students from SMP Islam Al-Manar, Bekasi, Indonesia. Participants were chosen purposively to represent different literacy levels. Data were collected through mathematical literacy tests and semi-structured interviews, then analyzed thematically to identify patterns in comprehension, algebraic reasoning, and contextual understanding. Result: The findings reveal that most students had a basic grasp of linear-equation concepts but faced challenges in connecting algebraic operations with everyday situations. Around sixty percent of them were categorized at low to moderate literacy levels, while only a small proportion about fifteen percent showed high literacy competence. Students with better conceptual understanding tended to demonstrate clearer reasoning and more structured strategies when solving contextual problems. Conclusion: Overall, students’ mathematical literacy in linear equations remains limited, particularly in transforming daily problems into mathematical forms. Enhancing this skill requires contextual learning approaches that promote independent exploration, critical reasoning, and authentic problem-based experiences. The insights gained from this study highlight the importance of designing learning models that bridge mathematical theory and practical application in junior high school education.